Taking Stock of Science Standards Implementation: Proceedings of a Virtual Summit - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On October 14 and 15, and December 8, 2021, the Board on Science Education at the National Academies of Sciences, Engineering, and Medicine held a virtual Summit entitled Taking Stock of Science Standards Implementation. Participants explored the landscape of state science standards implementation, identified where there have been successes and challenges, and determined next steps and the resources needed for continuing or re-invigorating implementation efforts. This publication summarizes the presentations and discussion of the event.
Keywords: Education

Rehabilitation of Culverts and Buried Storm Drain Pipes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Departments of transportation (DOTs) are increasing employment of asset management strategies in response to federal and state initiatives. Low-cost and effective treatments applied throughout the life of the asset can be employed prior to significant asset degradation, which otherwise would likely require a high-cost reactionary treatment.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 581: Rehabilitation of Culverts and Buried Storm Drain Pipes collects and summarizes rehabilitation practices (including full and partial rehabilitation) used by state DOTs for culvert and buried storm drain pipes.
Keywords: Transportation and Infrastructure

Taking Stock of Science Standards Implementation: Planning for Progress: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
It has been just over ten years since the release of the Framework on K-12 Science Education and the Next Generation Science Standards. As states continue their implementation efforts of state standards, there is a need for a reflection on these efforts looking at curriculum, instruction, assessment, professional learning, and policy. To identify the conditions and develop a road map for moving implementation efforts forward, the National Academies of Sciences, Engineering, and Medicine held a hybrid summit on April 26 and 27, 2022. Participants shared ideas to imagine what science education could look like in ten years, and how these visions might be achieved. This publication summarizes the presentation and discussion or the event.
Keywords: Education

Long-Term Impacts of COVID-19 on the Future Academic Careers of Women in STEM: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On March 23-24, 2022, the National Academies of Sciences, Engineering, and Medicine held a virtual workshop to explore the long-term impact of COVID-19 on the future careers of women in STEM. Workshop participants represented multiple sectors (i.e., higher education, government, and non-profit) as well as various career paths and stages (e.g., assistant, associate, and full professors; graduate students; program officers; directors; and policy advisors). The two-day workshop convened experts and leaders to outline a national research agenda that ensures academic institutions and federal agencies are able to monitor and mitigate the long-term negative impacts of the pandemic on the career trajectories, job stability, and leadership roles of women - especially women of color — in STEM. This publication highlights the presentation and discussion of the workshop.
Keywords: Policy for Science and Technology

Long COVID: Examining Long-Term Health Effects of COVID-19 and Implications for the Social Security Administration: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
'Long COVID' refers to the wide range of long-lasting symptoms experienced by some patients after a SARS-CoV-2 infection. The most common symptoms include fatigue, headache, brain fog, shortness of breath, hair loss, and pain. At this time, there are many knowledge gaps related to Long COVID, including the prevalence of the condition, the impact of the symptoms on survivors' ability to function, and the long-term course of the condition. While many individuals with Long COVID recover within one year, others experience little or no decrease in symptom severity over time. Long COVID symptoms can affect a person's ability to work and otherwise function in daily life, so people with the condition may need to utilize programs such as Social Security Disability Insurance (SSDI) and the Supplemental Security Income Program (SSI). The Social Security Administration (SSA), which administers both of these programs, requested that the National Academies of Sciences, Engineering, and Medicine host a public workshop to discuss research into the long-term health effects of COVID-19, their impacts on individuals and populations, and how the SSDI and SSI programs can support individuals who suffer disability as a result of Long COVID. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Assessment of the SBIR and STTR Programs at the National Institutes of Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The National Institutes of Health (NIH) asked the National Academies of Sciences, Engineering, and Medicine to conduct a quadrennial review of its Small Business Innovation Research (SBIR) and Small Business Technology Transfer (STTR) programs, in accordance with a legislative mandate. Using quantitative and qualitative analyses of data, this report reviews the operations and outcomes stemming from NIH's SBIR/STTR awards. Drawing on published research and conducting new analyses based on both publicly available data and applicant data provided by NIH, Assessment of the SBIR and STTR Programs at the National Institutes of Health analyzes (1) the effectiveness of NIH's processes and procedures for selecting SBIR and STTR awardees; (2) the effectiveness of NIH's outreach to increase SBIR and STTR applications from small businesses that are new to the programs, from underrepresented states, and from woman-owned and minority-owned businesses; (3) collaborations between small businesses and research institutions resulting from the programs; and (4) a range of direct economic and health care impacts attributable to the programs.
Keywords: Policy for Science and Technology

Toward a Transformational Africa-U.S. STEM University Initiative: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
STEM (science, technology, engineering, and mathematics) plays a key role in accelerating economic growth and developing innovative solutions to pressing challenges facing the African continent. Over the past few decades, much work has been done to develop university systems in African countries in recognition of the role that high-caliber teaching and research in STEM fields play in economic development. African universities and their governments have made many of these gains through partnering across countries and sectors. Often, however, these efforts are based on individual connections and do not lead to long-term change. Inspired by STEM's potential to tackle African and global challenges, a group of academic leaders has come together to explore a synergistic approach to transform African institutions of higher education and increase the global engagement of U.S. institutions. They developed an initial vision for a next-generation Africa-U.S. STEM initiative that would take place for at least 10 years, with funds of at least $10 million annually from governments, the private sector, philanthropies, and other organizations. To obtain input from stakeholders on how such an initiative could develop, the group held a virtual workshop March 14-16, 2022, convened by the National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions of the workshop.
Keywords: Education

Imagining the Future of Undergraduate STEM Education: Proceedings of a Virtual Symposium - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In November 2020, the National Academies of Sciences, Engineering, and Medicine convened a multi-day virtual symposium on imaging the future of undergraduate STEM education. Speakers and participants pondered the future and the past and shared their goals, priorities, and dreams for improving undergraduate STEM education. Expert speakers presented information about today's students and approaches to undergraduate STEM education, as well as the history of transformation in higher education. Thoughtful discussions explored ideas for the future, how student-centered learning experiences could be created, and what issues to consider to facilitate a successful transformation. This publication summarizes the presentation and discussion of the symposium.
Keywords: Education

Long-Term Infrastructure Program Letter Report: January 31, 2022 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
A January 31, 2022 letter report from TRB's Committee for the Review of Federal Highway Administration (FHWA) Infrastructure R&D Program's Long-Term Infrastructure Program (LTIP) summarizes recent program progress, strategic issues, and committee recommendations for future actions. The program has produced some useful products and results over the past year and continued to improve user accessibility to data and information.Although FHWA’s infrastructure research and development is considerably broader than the LTIP, the latter is the sole focus of this committee’s efforts. The LTIP collects long-term performance data on the condition of bridges and pavements that are valuable for guiding decisions regarding the maintenance, repair, and replacement of vital transportation infrastructure assets.
Keywords: Transportation and Infrastructure

Exploring the State of the Science of Stem Cell Transplantation and Posttransplant Disability: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Board on Health Care Services of the National Academies of Sciences, Engineering and Medicine hosted a virtual workshop, funded by the Social Security Association, to examine disability associated with hematopoietic stem cell transplantation. The workshop, held on November 15, 2021, included presentations on the functional outcomes for individuals who have received hematopoietic stem cell treatment, as well as medical advances, developments, and research in this area. This Proceedings of a Workshop highlights the presentations and discussions that occurred in the workshop.
Keywords: Health and Medicine

Attributes of a First-in-Class Environmental Program: A Letter Report Prepared for the Bureau of Ocean Energy Management - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Bureau of Ocean Energy Management (BOEM) manages the energy and mineral resources on the outer continental shelf. BOEM's environmental program, by producing environmental studies and conducting environmental assessments, ensures that environmental protection is a critical element of BOEM's decision making. This report addresses BOEM's aspirations to conduct a first-in-class science program within their Environmental Studies Program (ESP). This report describes attributes identified by the committee of a first-in-class, use-inspired, management-oriented science program (in this case, BOEM's ESP and its connection to the broader BOEM environmental program). The report recommends that BOEM develop procedures and conduct regular evaluations to assess whether and how well its environmental program meets the attributes of a first-in-class program and identify areas for improvement. It also outlines a framework for conducting such an evaluation. The report contains guidance and examples drawn from a workshop series with BOEM's peer agencies and other science programs, as well as other information gathering efforts. The guidance contained in this report is offered to BOEM as a starting point for developing more detailed processes for evaluating and improving its program.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation; Earth Sciences

Roadside Barrier Designs near Bridge Rail Ends with Restricted Rights-of-Way: A National Survey and Testing Reports (The National Academies Press, 2022)
The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 334: Roadside Barrier Designs near Bridge Rail Ends with Restricted Rights-of-Way: A National Survey and Testing Reports includes appendices to NCHRP Research Report 1013: Roadside Barrier Designs near Bridge Rail Ends with Restricted Rights-of-Way: A Guide, which describes the application and installation of short-radius guardrail systems for roadside barriers near bridge rail ends with restricted rights-of-way. The appendices provide further details on the literature review, state survey responses, plus crash-test analyses and results.
Keywords: Transportation and Infrastructure

Measuring and Understanding the Relationship Between Air Service and Regional Economic Development - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Airport economic impact studies may accurately measure the activity that occurs on airport properties or is tied directly to airport operations (such as off-site parking and hotels that accommodate airline crew who overnight in a location), but they do not capture how air service supports business and employment throughout the region. The TRB Airport Cooperative Research Program's ACRP Web-Only Document 53: Measuring and Understanding the Relationship Between Air Service and Regional Economic Development provides airports and major regional stakeholders concerned with economic development with the information and tools necessary to understand and communicate the nexus between air service and regional employment. The Web-Only Document is supplemental to ACRP WebResource 12: Air Service Development and Regional Economic Activity. Supplemental to the Web-Only Document is a Case Study Compilation with the full versions of the 14 case studies performed as part of the project.
Keywords: Transportation and Infrastructure

Frameworks for Protecting Workers and the Public from Inhalation Hazards - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Individuals in the United States and Americans abroad are exposed to inhalation hazards from a variety of sources, and these hazards can have both short- and long-term adverse effects on health. For example, exposure to wildfire smoke, which contains particulate matter and toxic chemicals, can lead to respiratory problems, increased risk for heart attacks, and other adverse health outcomes. Individuals also may be exposed to airborne infectious agents through aerosol or droplet transmission, and as demonstrated by the COVID-19 pandemic, the individual and public health consequences of these exposures can be severe. Storms, floods, and hurricanes can increase exposure to moisture-driven hazards, such as mold, and to accidental releases from production facilities or transport vehicles that may result in chemical exposures. The current regulatory system is focused primarily on ensuring access to respiratory protection in occupational settings characterized by well-defined hazards and employer-employee relationships. With this narrow regulatory focus, the respiratory protection needs of the public and many workers are not being met. As climate change increases the incidence and severity of wildfires, hurricanes, floods, infectious disease outbreaks, and other phenomena that impact air quality and human health, it is imperative that the United States ensure that the respiratory protection needs of the public and all workers are met. Recognizing the urgent need to address the gaps in the nation's ability to meet the respiratory protection needs of the public and workers without workplace respiratory protection programs, this report makes recommendations for a framework of responsibilities and authorities that would provide a unified and authoritative source of information and effective oversight for the development, approval, and use of respiratory protection.
Keywords: Health and Medicine

Leveraging the Future Research and Development Ecosystem for the Intelligence Community—Understanding the International Aspect of the Landscape: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 9, 2021, the Intelligence Community Studies Board of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on behalf of the Office of the Director of National Intelligence. This unclassified workshop was the second of two data-gathering workshops.
Keywords: Policy for Science and Technology

Leveraging the Future Research and Development Ecosystem for the Intelligence Community by the U.S. Research Community: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On April 19, 2021, the Intelligence Community Studies Board of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on behalf of the Office of the Director of National Intelligence. This unclassified workshop was the first of two data-gathering workshops.
Keywords: Policy for Science and Technology

Developing a Guide for Managing Performance to Enhance Decision-Making - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Transportation agencies largely have performance structures in place, but these structures alone do not guarantee progress on meeting performance targets.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 317: Developing a Guide for Managing Performance to Enhance Decision-Making provides guidance on how agencies can strengthen their gathering and use of feedback to inform actions and performance activities.The document is supplemental to NCHRP Research Report 993: Managing Performance to Enhance Decision-Making: Making Targets Matter.
Keywords: Transportation and Infrastructure

Using Biology for Communication and Information Transmission: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The digital age has transformed daily life and economies worldwide. While today's technologies store, compute, and transmit data at unprecedented volume and speed, there are potential applications for new paradigms of communication and information transmission. Harnessing biological processes and platforms could open new opportunities for durable and efficient data storage, powerful computational capabilities, and innovative approaches to sensing and peer-to-peer information transmission. Application of these technologies may also lead to new policy, security, and ethics challenges. To examine how cutting-edge biotechnologies and research could enable these new approaches, as well as the societal impacts they might have, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop on Using Biology for Communication and Information Transmission on January 20-21, 2022. This publication summarizes the presentation and discussion of the workshop.
Keywords: Biology and Life Sciences

Measurement and Analysis of Public Opinion: An Analytic Framework - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Intelligence analysts conduct these analyses every day, using decades of propriety tradecraft techniques and an arsenal of clandestine information gathering sources, but the resources available are not unlimited. Open source public opinion tools can provide timely and relatively inexpensive methods of understanding fast-moving conditions, acting as a force multiplier to help policymakers have a truly all-source understanding of complex events. By providing analysts with the best practices in survey methodology and nonsurvey methods for gathering data on public opinion, they will be armed with a clearer sense of important shifts in attitudes, elections, and unrest. In order to provide guidance to analysts on strategies for assessing public opinion, representatives from the intelligence community approached the National Academies of Sciences, Engineering, and Medicine to request preparation of a framework on Measuring and Analyzing Public Opinion. This analytic framework includes three layers of information. Layer 1 comprises four authored papers that review literature from various disciplines containing overview information as well as how the topic/situation of interest can enable better analysis across different situational constraints. Layer 2 is a distilled layer of information in the form of an authored summary of the four Layer 1 papers, both summarizing and describing key points. Finally, Layer 3 provides an even further distillation of the key concepts, in a one-page visual graphic, that displays key drivers from the work in Layers 1 and 2 to help the intended audience apply knowledge to the situation of interest.
Keywords: Behavioral and Social Sciences

Review of the Continued Analysis of the Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #1 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The Hanford Nuclear Reservation, where about two-thirds of the nation's weapons plutonium was produced from 1944 to 1987, is the site of the largest and most complex nuclear cleanup challenge in the United States. Section 3125 of the National Defense Authorization Act for Fiscal Year 2021 calls for a Federally Funded Research and Development Center (FFRDC) to develop a framework of decisions to be made among the supplemental treatment technologies, waste forms, and disposal locations for low-activity waste in the Hanford tanks. In addition, Section 3125 calls for the National Academies of Sciences, Engineering, and Medicine to provide a concurrent, independent peer review of the ongoing FFRDC analysis. This review report, the first of three to address the Congressional mandate, focuses on the technical quality and completeness of the FFRDC's draft framework.
Keywords: Environment and Environmental Studies